2012
DOI: 10.1117/1.jbo.17.10.106011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and quantification of spectral information in tissue by confocal microscopy

Abstract: Abstract. A confocal imaging and image processing scheme is introduced to visualize and evaluate the spatial distribution of spectral information in tissue. The image data are recorded using a confocal laser-scanning microscope equipped with a detection unit that provides high spectral resolution. The processing scheme is based on spectral data, is less error-prone than intensity-based visualization and evaluation methods, and provides quantitative information on the composition of the sample. The method is te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…An HSI system has been combined with many other techniques, such as laparoscope, 46 colposcope, 34 fundus camera, 76,113,114 and Raman scattering, 115 in order to leverage the key benefits of each instrument individually and provide more useful information for disease diagnosis and treatment. The most common combination is with microscope 35,38,85,[116][117][118][119][120][121] or confocal microscope, 122 which has been proved useful in the investigation of the spectral properties of tissue.…”
Section: Combination With Other Techniquesmentioning
confidence: 99%
“…An HSI system has been combined with many other techniques, such as laparoscope, 46 colposcope, 34 fundus camera, 76,113,114 and Raman scattering, 115 in order to leverage the key benefits of each instrument individually and provide more useful information for disease diagnosis and treatment. The most common combination is with microscope 35,38,85,[116][117][118][119][120][121] or confocal microscope, 122 which has been proved useful in the investigation of the spectral properties of tissue.…”
Section: Combination With Other Techniquesmentioning
confidence: 99%
“…220 In addition, the spectral confocal microscopes have also been used for fluorescence evaluation and quantification in different tissues, such as brain slices, mouse ovaries, skin sections, kidney slice, and breast cancer tissues. 134,221,222 Neher et al demonstrated that quantitative FRET can be performed by taking advantage of steady-state intensity measurements, but it only allows determination of the apparent FRET efficiency, the relative concentration of donor, and the concentration of the acceptor. 223 They also developed a nonnegative matrix factorization (NMF) algorithm to detect and separate spectrally distinct components of multiple labeled fluorescence images.…”
Section: Fluorescence and Cytogeneticsmentioning
confidence: 99%
“…237 Maeder et al introduced a confocal laser-scanning microscope equipped with a detection unit that provides high spectral resolution method to visualize and evaluate the spatial distribution of spectral information in skin sections. 221 In a more recent study by Nallala et al, an IR spectral imaging system was used for histopathological recognition in colon cancer diagnosis. 238 Fourier transform IR spectral imaging system has also been used to perform the histopathology mapping of biochemical changes in myocardial infarction, live epithelial cancer cells, histologic and biochemical correlations in tissue engineered cartilage, and histomorphological evaluation of oral squamous cell carcinoma of the oral cavity.…”
Section: Histological Analysismentioning
confidence: 99%
“…Since the vital nerve structures in the prostate are embedded in a fibrofatty plate in the pelvic region 47 , 51 , a dual fluorophore staining protocol using Oxazine 4 to highlight nerves and Nile Red to delineate adipose was also developed to mitigate non-specific adipose fluorescence, which would diminish nerve SBR. Nile Red is a fluorogenic, lipid-specific oxazine fluorophore that is spectrally distinct from Oxazine 4 52 - 56 , facilitating separation of nerve and adipose tissue fluorescence using a two-color imaging strategy. Translation of the optimized direct administration methodology to radical nerve-sparing prostatectomy could significantly improve cavernous nerve visualization and preservation, decreasing patient morbidity and improving post-surgical quality of life for prostate cancer survivors.…”
Section: Introductionmentioning
confidence: 99%